Tree co-occurrence and transcriptomic response to drought. Issue 1 (December 2017) - Swenson, Nathan; Iida, Yoshiko; Howe, Robert; Wolf, Amy; Umaña, María; Petprakob, Krittika; Turner, Benjamin; Ma, Keping
Abstract The distribution and co-occurrence of species are partly the outcome of their interactions with environmental drivers. Drought is a key driver related to the distribution of plant species. Drought events continue to increase in frequency and severity and identifying those aspects of plant function that are related to drought is critical. Here, we perform a community-level analysis of gene expression in relation to experimental drought and relate the similarity in gene set enrichment across species to their natural co-occurrence. Species with similar gene set enrichment in response to experimental drought tend to non-randomly co-occur in a natural stand. We demonstrate that similarity in the transcriptomic response of species to drought is a significantly better indicator of natural co-occurrence than measures of functional trait similarity and phylogenetic relatedness and that transcriptomics has the capacity to greatly enhance ecological investigations of species distributions and community structure. Drought has a major influence on plant distribution. Here, Swenson et al. show that a similar gene expression response to experimental drought outperforms traditional functional traits and phylogenetic relatedness as a predictor of co-occurrence of tree species in a natural stand.